Endemic Dietary Herb Extracts Reduce Acrylamide and Enhance Sensory Characteristics of Potato Chips - Daniel Assefa; Engida Dessalegn; Kebede Abegaz (Journal of Food Protection)
This study evaluated the impact of soaking potato slices in water containing extracts from three endemic herbs, Lippia adoensis var. adoensis (kesse), Lippia adoensis var. koseret (koseret), and Thymus schimperi Ronninger (tosign), on acrylamide content and sensory attributes of fried potato chips. The total phenolic content (TPC) and total flavonoid content (TFC) of the extracts were measured using the Folin-Ciocalteu and aluminum chloride colorimetric methods, respectively. Antioxidant activity was assessed using ferric-reducing antioxidant power (FRAP) and ferrous chelating activity (FICA). Acrylamide levels were quantified using high-performance liquid chromatography (HPLC), while sensory attributes, including taste, color, odor, crispiness, and overall acceptability, were assessed. Kesse extract exhibited the highest TPC (30.20 ± 1.23 mg GAE/g) and TFC (15.87 ± 1.06 mg QE/g), FRAP (63.95 ± 1.53 μg/mL), and FICA (110.15 ± 3.27 μg/mL). Potato chips treated with kesse extract reduced acrylamide levels to 0.576 mg/kg (63.4%), followed by tosign (0.654 mg/kg, 58.5%) and koseret (0.870 mg/kg, 44.8%), while butylated hydroxytoluene (BHT) achieved a reduction to 1.097 mg/kg (30.4%) compared to the control (1.58 mg/kg). A significant negative correlation was observed between TFC (R2 = 0.9956) and TFC (R2 = 0.8802) with acrylamide levels (p < 0.05). Sensory evaluation revealed that potato chips treated with kesse extract scored significantly higher in taste, odor, and color, leading to enhanced overall acceptability. These findings demonstrate the potential of these endemic dietary herbs as natural antioxidants to mitigate acrylamide formation and improve the sensory quality of potato chips, suggesting practical applications in food processing and health-conscious diets.